Dorsolateral prefrontal cortex and amygdala function during cognitive reappraisal predicts weight restoration and emotion regulation impairment in anorexia nervosa - Steward, Trevor; Martínez-Zalacaín, Ignacio; Mestre-Bach, Gemma; Sánchez, I.; Riesco, N.; Jiménez-Murcia, Susana; Fernández-Formoso, J.A.; Veciana de las Heras, Misericordia; Custal, N.; Menchón, José M.; Soriano-Mas, Carles; Fernandez-Aranda, Fernando (Cambridge University Press, 2022)
BackgroundAlthough deficits in affective processing are a core component of anorexia nervosa (AN), we lack a detailed characterization of the neurobiological underpinnings of emotion regulation impairment in AN. Moreover, it remains unclear whether these neural correlates scale with clinical outcomes.MethodsWe investigated the neural correlates of negative emotion regulation in a sample of young women receiving day-hospital treatment for AN (n = 21) and healthy controls (n = 21). We aimed to determine whether aberrant brain activation patterns during emotion regulation predicted weight gain following treatment in AN patients and were linked to AN severity. To achieve this, participants completed a cognitive reappraisal paradigm during functional magnetic resonance imaging. Skin conductance response, as well as subjective distress ratings, were recorded to corroborate task engagement.ResultsCompared to controls, patients with AN showed reduced activation in the dorsolateral prefrontal cortex (dlPFC) during cognitive reappraisal [pFWE<0.05, threshold-free cluster enhancement (TFCE) corrected]. Importantly, psycho-physiological interaction analysis revealed reduced functional connectivity between the dlPFC and the amygdala in AN patients during emotion regulation (pFWE<0.05, TFCE corrected), and dlPFC-amygdala uncoupling was associated with emotion regulation deficits (r = -0.511, p = 0.018) and eating disorder severity (r = -0.565, p =.008) in the AN group. Finally, dlPFC activity positively correlated with increases in body mass index (r = 0.471, p = 0.042) and in body fat mass percentage (r = 0.605, p = 0.008) following 12 weeks of treatment.ConclusionsTaken together, our findings indicate that individuals with AN present altered fronto-amygdalar response during cognitive reappraisal and that this response may serve as a predictor of response to treatment and be linked to clinical severity. © 2020 The Author(s),. Published by Cambridge University Press.
Keywords: anorexia nervosa; cognitive reappraisal; eating disorders; emotion regulation; fMRI; Scopus; JCR